Crystal structure of a polymorph of potassium picrate, C6H2KN3O7 - Luo Xinyao; Chen Cuilian; Hu Zunjian; Wang Fei; Sun Shanhu; Suo Zhirong; Su Li (Zeitschrift für Kristallographie - New Crystal Structures)
C6H2KN3O7, monoclinic, P21/m (no. 11), a = 4.1681(2) Å, b = 10.6704(6) Å, c = 10.2381(6) Å, β = 95.134(2)°, V = 453.52(4) Å3, Z = 2, R gt(F) = 0.0404, wR ref(F 2) = 0.0967, T = 295 K.